A high performance cathode for proton conducting solid oxide fuel cells1. Issue 16 (28th April 2015) - Wang, Zhiquan; Yang, Wenqiang; Shafi, Shahid P.; Bi, Lei; Wang, Zhenbin; Peng, Ranran; Xia, Changrong; Liu, Wei; Lu, Yalin
<x xml:space="preserve">Abstract</x> Intermediate temperature solid-oxide fuel cells (IT-SOFCs) have become a need worldwide due to their greater fuel efficiency, lower air pollution, much reduced cost and excellent longtime stability in energy conversion devices.